Avaliação de desempenho térmico em edificações multifamiliares considerando o impacto das mudanças projetadas para o clima futuro - Machado, Jessica de Mello (2019)
In the late decades, the scientific community have noticed changes in the climate patterns, indicating a warming trend on the average global temperature, in the long run. This warming trend which will lead to great environmental impacts over the life conditions on the planet. The thermal behavior and consequently the energetic consumption by buildings will be severely affected. Therefore, the existing construction as far as the new ones will require adjustment. The passive design strategies are valuable solutions to increase building performance in favor of the energy efficiency. The main goal was evaluating the thermal performance of multifamily residency building naturally ventilated, placed in different Brazilian climate contexts, considering passive strategies to mitigate the impact of climate change. The adopted methodology was segmented in three major steps. Initially it was selected the computational tool Climate Change World Weather File Generator in order to create future climate files, relative to years of 2020, 2050, and 2080 . These years were selected using as basis the A2 scenery from Intergovernmental Panel on Climate Change – IPCC, established for the cities of Manaus, Brasília, Porto Alegre e Vitória. To validate the evaluation, a hypothetical multifamily residential typology was considered, designed as representative buildings built in Brazil. From the hypothetical model, measurements were proposed for passive adaptation based on the Brazilian norm NBR 15220:3-2008. Thermal simulations were ran using the two parametric models assembled in the software DesignBuilder. The performance evaluation was done through indexes of frequency and hours-grade of thermal discomfort and the results have shown levels of thermal discomfort for the two models simulated. The retrofit proposal revealed significant improvements for all the cities, yet with thermal discomfort. Therefore, it was found that the adoption of suitable bioclimatic strategies can contribute for comfort improvements into internal space. However, when the climate changes for the future period are considered, other ways of readjustment will be necessary, either for the building or for normative proposals, emphasizing the idea that every building should be designed for the future, not for the past.